La percepción de la mujer respecto a su feminidad, al convertirse en madre, en relación al lugar que considera le es otorgado por el otro - Mediavilla Simbaña, Diana Paola (2013)
The following paper pretends to analyze the woman perception that became mother, in relation to the place she considers is granted by the Other. Such discussion is made from psychoanalytic theory, it describes main concepts which are feminity and maternity, the perception despite not being a widely used term in psychoanalysis is explained by Lacan's perspective and other areas. Also it tries to identify the place where the mother could be located in the discourse of the Other. It takes a chronological travel by the main psychoanalytic concepts from several authors, principally Freudian and Lacanian texts. The research method used is a descriptive bibliographic review by the cualitative approach. The found results, show that femininity could be explained by developing in which the girl become in woman identifying with her mother and taking her father like the new love object, social intervention could influence on the feminity development by the Symbolic. Also the relationship with the other sex and with her mother could influence in the feminity construction The present paper concludes that it doesn't exist an specific kind of perception, but the viewpoint mentioned above could likely intervene in the perception of the woman that becomes mother, the perception is built through the relationship of the person with the language and belongs to the Symbolic order.